Karakterisasi Virus Penyebab Penyakit Belang pada Tanaman Lada (Piper nigrum L.) - Trisnani Alif; Sedyo Hartono; Sri Sulandari (Universitas Gadjah Mada, 2018)
Mottle disease is an important disease in pepper plants caused by Piper yellow mottle virus (PYMoV). This study aims to determine the characterization of PYMoV biologically and molecularly. The pepper plant samples were obtained from pepper farmland in Kleben, Putat (Yogyakarta), and Air Buluh (Bangka). Virus particles are measured by electron microscopy. Virus transmission studies include mechanical transmission, vector, cuttings, grafting, and seeds. The molecular detection was done by using Polymerase chain reaction (PCR) method with PYMoV-F and PYMoV-R specific primers. The result, virus particles were found to be ± 30×130 nm in shape. Virus transmission studies indicate that PYMoV can be transmitted by Ferrisia virgata vectors, cuttings, grafts and seeds but cannot be transmitted through mechanical inoculation. Molecular test results showed that samples of Kleben, Putat and Air Buluh pepper plants were positively detected to contain PYMoV and amplified at 400 bp. The result of nucleotide base sequence analysis showed the isolates of Putat and Air Buluh had the highest homology with PYMoV of India 2 about 95% while Kleben isolate had 96% homology with PYMoV of India 1. IntisariPenyakit belang merupakan salah satu penyakit penting pada tanaman lada yang disebabkan oleh Piper yellow mottle virus (PYMoV). Penelitian ini bertujuan untuk mengetahui karakterisasi PYMoV secara biologi dan molekuler. Sampel tanaman lada diperoleh dari lahan petani lada di Desa Kleben, Putat (Yogyakarta), dan Air Buluh (Bangka). Partikel virus diukur dengan mikroskop elektron. Kajian penularan virus meliputi penularan mekanik, vektor, stek, penyambungan, dan biji. Deteksi secara molekuler dengan metode Polymerase chain reaction (PCR) dengan pasangan primer spesifik PYMoV-F dan PYMoV-R. Partikel virus yang ditemukan berukuran ± 30×130 nm berbentuk batang. Kajian penularan virus menunjukkan bahwa PYMoV dapat ditularkan melalui vektor Ferrisia virgata, stek, penyambungan dan biji namun tidak dapat ditularkan melalui inokulasi mekanik. Hasil uji molekuler menunjukkan bahwa sampel tanaman lada Kleben, Putat dan Air Buluh positif terdeteksi PYMoV dan teramplifikasi pada 400 bp. Hasil analisis sekuen basa nukleotida menunjukkan isolat Putat dan Air Buluh memiliki homologi tertinggi dengan PYMoV India 2 sekitar 95% sedangkan isolat Kleben memiliki homologi 96% dengan PYMoV India 1.